(untitled) (American Journal of Islam and Society, 2005)
Richard Bonney laments what he deems a misappropriation of the term jihad by both pundits in the West seeking to portray Islam as inherently violent, and a small faction of Muslim fanatics seeking political gain. Jihad, he contends, has been perverted from its original intent of encouraging spiritual athleticism and allowing for physical defense when transgression occurs. He endeavors to return to the term’s roots to detail how and why it has been manipulated over time to take on exclusively violent and aggressive connotations. By doing so, Bonney hopes to empower Muslim moderates to publicize the concept of jihad as purely defensive, as well as to enlighten non-Muslims of Islam’s true message of peace, balance, and pluralism. The author goes back to the original sources, the Qur’an and the Sunnah, to make his case. He demonstrates his familiarity with the Qur’an by citing verses on jihad, contextualizing them in purely spiritual and defensive terms, and briefly mentions how they could be misinterpreted if one did not view the Qur’an holistically and in its proper context. However, Bonney betrays his ignorance of the Qur’anic sciences in his rather superficial description and application of classical hermeneutics and abrogation theory. Rather than engage the prolific tradition of Qur’anic exegesis, he relies on a few modern commentators (e.g., Qamaruddin Khan and Reuven Firestone) to promote his views. He acknowledges that these interpretations may differ with the tradition, but he does not address or attempt to resolve the tension between the two ...